A língua nas narrativas de descendentes de imigrantes alemães: pertencimento, silenciamento e memória - Carpenedo, Rejane Beatriz Fiepke (2023)
This Doctoral thesis is built from the German immigration language that circulates in a small municipality in the interior of Rio Grande do Sul, of mixed colonization, located in the northwest region of the State. The research proposes to analyze the space of enunciation and the functioning of the interdiscourse in the memories of descendants of immigrants present in their narratives. In addition to the secondary objectives of: analyzing what are the meanings and memories of the German Immigration Language enunciated by the descendants; identify how memories support identity belonging through Language; investigate how it happens and if there is a relationship with the spoken language and the written language; verify which are, and if there are, institutions that maintain the Immigration Language; and research whether there are memories or crossings of the Linguistic Policy of the Vargas Era in the narratives of descendant subjects. The theoretical perspective adopted is that of the Theory of Enunciation (Benveniste, 1989), more specifically focused on the assumptions of the Semantics of the Event (Guimarães, 2002; 2018), and working with concepts such as memory, belonging, meaning, interdiscourse and space of enunciation. The analytical movement is based on the assumptions of the theory, making use of the interpretation procedure supported by the Semantics of the Event itself, especially with regard to the meanings constituted by the interdiscourse and its functioning in the enunciation space. The analysis is based on a selection of 27 enunciative sequences from the narratives derived from the interviews carried out with the descendants of German immigrants. The analytical process showed how the meanings are constituted from the memories in the speeches of subjects descended from immigrants, categorizing themselves as belonging, silenced language and memory language; that is, three distinct axes of language functioning, which are also configured as three distinct spaces of enunciation. The research showed that the Language Policy of the Vargas Era, and through it the nationalized school, were factors that directly interfered in the maintenance of the mother tongue. On the other hand, families have been the space where language is still perpetuated today, through memory, affections and cultural practices. As well as, the absence of public policies to maintain the languages of immigration also contributes to their gradual silencing among the new generations.